Bridging the Digital Divide: An Analysis of AI and VR Integration for Equitable English Language Education - Talehati (European Journal of Social Science Education and Research, 2025)
This paper examines how Artificial Intelligence (AI) and Virtual Reality (VR) can be integrated to help encourage fair English language learning in a socially-based analysis framework. The research is based on the constructivist learning theory, the sociocultural theory suggested by Vygotsky, the Technology Acceptance Model (TAM), and the ideas of critical pedagogy and proposes the following concepts: immersive AI-VR environments can improve the motivation of learners, engage them, introduce socialization, and affect language outcomes. A two-way approach was considered that used 120 learners and 12 teachers on a period of 12 weeks. The quantitative data were measured by using pre- after language tests, motivation scales, and TAM questionnaires and qualitative data were gained by using interviews, observations, and reflective journals. The results have shown that the AI-VR application of integration greatly improves the quality of communicative competence, confidence, and collaborative interactions between learners. Nonetheless, structural issues like internet connectivity and connectivity remain as a barrier to fair adoption. The paper points out the promising nature of AI-VR technology when applied to eliminate the educational gaps and integrated into an inclusion-based pedagogical and policy framework.